2018
DOI: 10.1038/s41590-018-0272-2
|View full text |Cite|
|
Sign up to set email alerts
|

Self-renewing resident cardiac macrophages limit adverse remodeling following myocardial infarction

Abstract: Macrophages promote both injury and repair following myocardial infarction, but discriminating functions within mixed populations remains challenging. Here we used fate mapping and single-cell transcriptomics to demonstrate that at steady state, TIMD4 + LYVE1 + MHC-II lo CCR2 − resident cardiac macrophages self-renew with negligible blood monocyte input. Monocytes partially replaced resident TIMD4 − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
771
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 653 publications
(839 citation statements)
references
References 56 publications
58
771
3
7
Order By: Relevance
“…We also observed fast (gut and dermis) versus slow (kidney, spleen and peritoneum) RTM replacement. Others have shown that even within the same tissue, macrophage subpopulations with different phenotypes exhibit different turnover rates, including in the gut (De Schepper et al, 2018;Shaw et al, 2018), heart (Dick et al, 2019) and skin (Tamoutounour et al, 2013). Here, we confirmed that in the dermis, MHCII + macrophages are replaced at a faster rate than MHCIImacrophages (Tamoutounour et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed fast (gut and dermis) versus slow (kidney, spleen and peritoneum) RTM replacement. Others have shown that even within the same tissue, macrophage subpopulations with different phenotypes exhibit different turnover rates, including in the gut (De Schepper et al, 2018;Shaw et al, 2018), heart (Dick et al, 2019) and skin (Tamoutounour et al, 2013). Here, we confirmed that in the dermis, MHCII + macrophages are replaced at a faster rate than MHCIImacrophages (Tamoutounour et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although Tim-4 can be used for early time points, it is not suitable for later time points, again highlighting that murine tissues are often analyzed prematurely, when macrophage equilibrium is not reached, leading to inaccurate conclusions. Rather, Tim-4 should be considered as a marker of long-term macrophage residency in tissues(Dick et al, 2019). In a sterileScott et al, 2016).…”
mentioning
confidence: 99%
“…It is therefore of utmost importance to establish a precise baseline during 25 homeostasis as provided here by our new consensus map, to allow for a better understanding of any deviations of the myeloid cell compartment during stress, pathophysiological conditions and diseases. Furthermore, the dynamic processes of myelopoiesis during homeostasis but even more so during inflammatory conditions requires precise mapping of cellular identities as a prerequisite to identify targets for precise therapeutic intervention (Dick et al, 2019;Schultze, 2019;Schultze et al, 2019). Furthermore, the necessity to continuously iterate the process of 5 improving the consensus maps is nicely illustrated by the accompanying manuscript by Dutertre et al (Dutertre et al, 2019), further defining the cellular relationship of DC2/3 and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion Innate immunity and cardiac inflammation have recently been linked to heart failure (Sager et al, 2016;Bajpai et al, 2018;Dick et al, 2019), a connection that may contribute to the dismal survival rate of patients with recurrent MI (Thune et al, 2011). There were no available systems for modeling inflammatory circuits in recurrent MI.…”
Section: !mentioning
confidence: 99%